AN ASSESSMENT OF SCIENCE PROCESS SKILLS AMONG SCIENCE STUDENTS IN RIVER STATE, NIGERIA - B. Mirian , Olowu (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2023)
The present study assessed junior secondary school students' basic and integrated science process skills. The study was conducted during the 2021/2022 academic year in the post-primary education zones of River state, Nigeria. The participants completed a self-report measure of the SPS. A descriptive research method was adopted in the study. The percentage analysis conducted on the data revealed that most respondents (66.2%) were more familiar with the concept of basic science process skills than (33.8%) of their counterparts. Conversely, the result revealed high unfamiliarity with integrated science process skills among the students (84.4%). The finding revealed a gap in science teaching and learning in River state's post-primary education system. It is recommended that teachers improve their pedagogical strategies in the science classroom. The result has implications for developing science education.